Sick sinus syndrome. Case report and review of the literature (Boletin Médico de Postgrado, 2023)
The sick sinus syndrome is a group of arrhythmias due to the abnormal formation and conduction of the electrical impulse from the sinus node originated by an inherent node disturbance which avoids it to perform its pacemaker function. This syndrome has an incidence of 1/600 patients and it is the most frequent cause for pacemaker’s implantation. We present a case of an adult patient with sick sinus syndrome, evaluated and diagnosed in the Electrophysiology Unit of Ascardio in Barquisimeto, Venezuela, with the corresponding review of the literature.
Keywords: sinoatrial node; pacemaker, artificial; arrhythmias, cardiac; sick sinus syndrome; electrocardiography